A leitura de metáforas como evento social: a construção de sentidos em crônica de Arnaldo Jabor - Mendes, Liliam de Oliveira (2007)
This work, which takes part of Portuguese Language area, is an empirical research about metaphors reading found in a journalistic chronicle, and has as main purpose to verify what kinds of relations are established between the metaphor and readers expression in the comprehension process. It presents the reading - made by teachers during a reading event - of an Arnaldo Jabor s chronicle, which pressuposts were the indetermination of feelings and reading as a social co-construction process at interactionism. Therefore, the use of verbal protocol in group was detached at data collection. The study focused itself of which kinds of relations are established between the metaphors found in the chronicle and the readers voices trying to make sense. The readers that take part of this research are teachers that work at high school of a public school in the state of São Paulo. The empirical material was collected and analyzed in an ethnographic projection. The results shown that the metaphors reading were constructed into the interaction process with basis in relations established in knowledge acquired previously by readers, through the experience with other sources of knowledge structured in language. Thus, this study presented, by means of co-construction transacted in text meanings, the reading as an active process in which the communicative competence is used for the participants of this research, at the text comprehension